The interrelationship between genotype, sex, and dietary lysine effects on carcass characteristics in 230 and 280 lb finishing pigs - Friesen, K.G.; Weeden, T.L.; Richert, B.T.; Kats, L.J.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and twenty pigs (initially 96 lb BW) were slaughtered either at 230 lb (40 pigs) or at 280 lb (80 pigs) to determine the interrelationship between genotype, sex, and dietary lysine effect on carcass characteristics in a 2 x 2 x 2 factorial arrangement. Genetic comparisons were made between pigs characterized by either high or medium potential for lean tissue gain. Barrows and gilts were separately fed either .90 or .70% dietary lysine within genotype. One pig per pen was slaughtered for carcass evaluation at a pen mean weight of 230 lb, with the remaining two pigs fed .75 or .55% dietary lysine until a pen mean weight of 280 lb was obtained. At this point, the remaining two pigs were slaughtered for carcass evaluation. High lean-gain pigs slaughtered at 230 lb had a heavier chilled carcass weight and longer carcasses than medium leanrgain pigs. Gilts had larger loineye area and less backfat compared to barrows. Increased dietary lysine did not influence carcass characteristics at 230 lb. At 280 lb, high lean-gain pigs had increased hot carcass weight, chilled carcass weight, loineye area and carcass length compared to medium lean-gain pigs. Gilts had an increased dressing percentage, loineye area, and carcass length in conjunction with decreased backfat thickness and kidney fat compared to barrows. Increased dietary lysine did not influence carcass characteristics in pigs slaughtered at 280 lb. These data indicate that carcass characteristics were not influenced by genotype at 230 lb. However, in the group fed to 280 lb, high lean-gain pigs had superior carcasses compared to medium lean gain pigs. Carcass characteristics were optimized in gilts at either slaughter weight, suggesting that high lean-gain gilts can be fed to heavier weights without sacrificing carcass merit.
Keywords: Swine; Pigs; Genotype; Sex; Lysine; Backfat; Loineye area